On the Diophantine Equation 3x + p5y = z2 - LAIPAPORN, Kittipong; WANANIYAKUL, Saeree; KHACHORNCHAROENKUL, Prathomjit (Walailak Journal of Science and Technology (WJST), 2019)
In this paper, we present new series of solutions of the Diophantine equation 3x + p5y = z2 where p is a prime number and x; y and z are nonnegative integers using elementary techniques. Moreover, the equation has no solution if p is equivalent to 5 or 7 modulo 24.